Sisters like us [compact disc, unabridged] - Mallery, Susan (Mallery, Susan. Mischief Bay., 2018)
Separately they may be a mess, but together Harper and Stacey can survive anything: their indomitable mother, overwhelming maternity stores, and exes' weddings. This is a delightful look at sisters, mothers, and daughters in today's fast-paced world, told with Susan Mallery's trademark warmth and humor.